1998
DOI: 10.1152/ajpregu.1998.275.1.r105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leptin on energy balance does not require the presence of intact adrenals

Abstract: The present study was conducted to assess the effects of leptin on food intake and energy balance in the presence or absence of corticosterone. Three cohorts of C57BL/6 mice differing in their corticosterone status [nonadrenalectomized (intact), adrenalectomized (ADX), and ADX with corticosterone replacement] were infused with either saline or leptin at a dose of 150 μg ⋅ kg−1 ⋅ day−1. Throughout the study, mice had free access to both a high-starch and a high-fat diet. At the end of the experimental period, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
5
7
1
Order By: Relevance
“…Instead, increased weight plateaued upon HFD withdrawal. Whereas we cannot exclude a role of the adrenals in the phenotype we see, leptin action does not depend on intact adrenal glands29. Thus, the persistence of adiposity in regionally sympathectomized mice, as well as the defective responses to leptin, is consistent with the known role of sympathetic neuro-adipose junctions in driving lipolysis and fat mass reduction5.…”
Section: Discussionsupporting
confidence: 77%
“…Instead, increased weight plateaued upon HFD withdrawal. Whereas we cannot exclude a role of the adrenals in the phenotype we see, leptin action does not depend on intact adrenal glands29. Thus, the persistence of adiposity in regionally sympathectomized mice, as well as the defective responses to leptin, is consistent with the known role of sympathetic neuro-adipose junctions in driving lipolysis and fat mass reduction5.…”
Section: Discussionsupporting
confidence: 77%
“…Convincing demonstrations of the effects of glucocorticoids on food intake in animals have, however, been reported. 34,35 Whether or not these results can be transposed to humans remains unclear, but our results seem to support observations from the animal literature. It is however unclear as to why cortisol comes Weight loss and appetite E Doucet et al out as such a strong predictor of changes of VAS variables.…”
Section: Weight Loss and Appetite E Doucet Et Alsupporting
confidence: 83%
“…At the end of 10th week of the high-calorie diet, rats had significantly increased body weights, eventually being 20% heavier than control rats (pϽ0.001), which was in agreement with previous reports that showed that feeding the high-calorie diet developed obesity in several rodent models. [9][10][11] Feeding with diet which has high lipid proportion has developed obesity and adipose tissue mass increase. Therefore, leptin levels also have shown elevations.…”
Section: Discussionmentioning
confidence: 99%